Intellectual Capital: A Critical Approach on Definitions and Categorization - Diana Gioacasi (CES Working Papers, 2014)
Intellectual capital has become the leading resource for creating economic value and there are an important number of publications focused on this area of research. In spite of the interest for this area of research, the existence of different terms regarding intellectual capital makes the process of definition and classification difficult. The purpose of this study is to analyze the concepts related to intellectual capital by establishing the connections and correlations between the terms in order to make the term of intellectual capital fully understandable and also to explain how the components of intellectual capital can be structured. The analysis of intellectual capital definitions is significant because it is a first step in intangible factors understanding, having implications on the company pattern of knowledge evaluation. Of all the terms analyzed, intangible assets allows a clear definition of its meaning, its components and thus provides insight into ways of assessing the knowledge of an entity.
Keywords: M14; M41; D23; D83; 330; intellectual capital; intangible assets; knowledge management; intangible resources